2020
DOI: 10.1142/s0218127420502077
|View full text |Cite
|
Sign up to set email alerts
|

The Structural Stability of Maps with Heteroclinic Repellers

Abstract: This note is concerned with the effect of small [Formula: see text] perturbations on a discrete dynamical system [Formula: see text], which has heteroclinic repellers. The question to be addressed is whether such perturbed system [Formula: see text] has heteroclinic repellers. It will be shown that if [Formula: see text] is small enough, [Formula: see text] has heteroclinic repellers, which implies that it is chaotic in the sense of Devaney. In addition, if [Formula: see text] and [Formula: see text] has regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Since Li and Yorke first introduced the term "chaos" in 1975 [1], chaotic dynamics have been observed in various fields [2][3][4][5][6][7][8][9][10]. When chaotic theory was in its initial stage, Marotto generalized the results of Li and Yorke in interval mapping to multidimensional discrete systems and proved that a snapback repeller implies chaos [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since Li and Yorke first introduced the term "chaos" in 1975 [1], chaotic dynamics have been observed in various fields [2][3][4][5][6][7][8][9][10]. When chaotic theory was in its initial stage, Marotto generalized the results of Li and Yorke in interval mapping to multidimensional discrete systems and proved that a snapback repeller implies chaos [11].…”
Section: Introductionmentioning
confidence: 99%
“…Chen and Li provided a sufficient condition of a high-dimensional difference equation having symbolic embedding for enough small C 1 perturbations [22]. In 2020, Chen and Wu et al showed that the system with heteroclinic repellers has the structural stability in [4,16].…”
Section: Introductionmentioning
confidence: 99%